Students' Perception on The Use of Project-Based Learning in Writing Activity at SMAN 7 Padang - Zulfi, Nurul Febiola; Fitrawati, Fitrawati (Universitas Negeri Padang, 2024)
Project-based learning is intended to provide opportunities for students to advance their English skills. Writing is one of the English abilities that students should learn in their English classes. This research intended to figure out the students’ perception on the use of project-based learning in writing activity. This was a survey study with a quantitative methodology, with data collected through a questionnaire. There was 51 students from 11th-grade students of SMAN 7 Padang who learned English using Project-based learning for writing activities became the sample of this study. They were given 25 questions to find out their perception of the use of project-based learning in writing activity. The result indicated that most of the students had positive perceptions about the use of project-based learning in their writing activity. In addition, the use of project-based learning received a positive view that involves engaging the students to produce English texts.